Microcontroller-Based Spectrum Analyzer System - Kritharan, Rajandran (2022)
The role of the spectrum analyzer becomes very important for song editors and audio engineers to assess their work; however, it turns out that spectrum analyzer for these needs is still difficult to find, which generally exists only for needs with a limited frequency range for other needs besides song correction needs that require a 32-band audio signal spectrum. This paper introduces a design of efficient and low-cost audio spectrum analyzer using Arduino board to analyze signal spectrum in 32-band audio. Spectrum analyzer for 32-band audio signal spectrum generally integrated in a set of audio system devices that are relatively expensive and not separated, even though not all features of the audio analyzer are used. Fast Fourier Transform (FFT) implemented in this spectrum analyzer. The audio spectrum analyzer system has been designed around the microcontroller (Arduino MEGA Board) which is available with an Analog to Digital Converter (ADC) feature that is used to convert audio input signals into digital samples. The ADC is configured to sample the input signal with clock frequency of 38.46 kHz. This achieved by configuring the ADC pre-scaler to 32. Sampling frequency of 38.64 kHz means that digital samples can reproduce input frequencies up to 19.32 kHz (Nyquist theorem) which is good enough for audio signals. The system collects audio signal and audio analysis is designed based on this scheme. The software has been developed using MATLAB where the result analysis will be displayed. The result analysis from the audio spectrum analyzer can be used as audio or music correction, the 32-band audio graphic bar will show if the audio signal run properly.